Integrative indexes reveal the tolerance of winter wheat to different overwinter freezing injury - Wu, Lu; Yu, Weidong; Cheng, Chen; Feng, Liping; Yan, Jintao; Zheng, Dawei; Yang, Feiyun (Frontiers in Plant Science, 2024)
Winter wheat (Triticum aestivum L.) is a crucial crop that guarantees food supply in the North China Plain (NCP). As the frequency of extreme cold events increases, it is necessary to explore the freezing resistance of different wheat varieties in order to clarify planting boundaries and help with risk assessment. In this study, 2-year controlled experiments were conducted to explore the effect of freezing temperatures (Tair) and freezing durations on three winterness types. A set of indexes were used to characterize the subfreezing stress on wheat tiller, leaf, and final yield. Logistical regressions were used to quantify the temperature threshold for 10%, 30%, and 50% of freezing injury. The results showed that the lower temperature threshold of tiller (LT) varied from −9.6 to −15.9°C, −10.7 to −19.1°C and −11.4 to −21.2°C for LT10, LT30, and LT50, respectively. The difference between LT and yield loss (YL) indexes reduced with decreased winterness types and was −0.1 to 3.4°C, −0.7 to 2.1°C, and 0.3 to 0.9°C higher compared with YL thresholds for winterness, semi-winterness, and weak-winterness types, respectively. The average minimum soil temperature was 7.5, 4.8, and 4.2°C higher than Tair for 1-, 2-, and 3-day treatment, respectively. Soil effective negative accumulated temperature hours (TSEh) ranged from 6.9 to 12.0, 48.4 to 6.9, and 84.7 to 106.9°C·h for 10%, 30%, and 50% tiller mortality, respectively. Freezing treatment with Tair < −12, −9, and −8°C obviously decreased leaf Fv/Fm for the three varieties and Fv/Fm declined obviously after 5 days of recovery under field conditions. Our results provided multiple indexes for quantifying subfreezing damage in practical wheat production and could shed light on future risk assessment.